The difficulties of environmental responsibility and ways of settling their international disputes - Mohamed, Sami El Tayeb Idris (Journal of Economic, Administrative and Legal Sciences, 2017)
This paper dealt with procedural and substantive difficulties faced by environmental responsibility and how to overcome them, in addition to resolving environmental disputes ways. The study relied to collect and extract information from the main sources as references and basic books, research and scientific papers, lectures, and some national legislation and then take advantage of this information to come to the results of scientific value. This study was to identify the problems facing environmental responsibility, the study responded to a query search in terms of the nature of those problems and how to overcome them, where the researcher found during the study to several conclusions, perhaps the most notable: Approval of jurisprudence inadequacy tort techniques in its traditional form to overcome environmental protection problems. There are still difficulties in determining the basis of liability for environmental damage for being the place of doctrinal disputes have not been resolved conclusively because of the special nature of the environmental damage. The difficulty of self-responsibility in the field of environmental protection not only domestically but also just appeared on the international level. The financial compensation arranged by the environmental damage has not received wide acceptance in the field of environmental protection. The nature of international relations in the light of regional and international blocs, making negotiations more vital roads and palatable to solve environmental disputes. Based on these findings the study found several      recommendations, perhaps the most important: the adoption of the application of all legal techniques to sort of responsibility in the field of environmental protection. Give environmental associations the right to legal representation to curb attacks on the environment. Oblige all industrial enterprises to take environmental measures. Develop the concept of diplomatic protection and international direct responsibility procedural rules relating to the settlement of environmental disputes in addition to the application of the theory of strict liability. To work on activating the consultative role of the International Court of Justice in resolving environmental disputes.
Keywords: difficulties; responsibility; environmental; settlement; international